Activation of polymer electrolyte membrane fuel cells: Mechanisms, procedures, and evaluation. (12th July 2022) - Pei, Pucheng; Fu, Xi; Zhu, Zijing; Ren, Peng; Chen, Dongfang
Abstract: Newly fabricated proton exchange membrane fuel cells (PEMFCs) need an activation process to improve the initial performance. The long activation time leads to a high cost and a low production efficiency, thus it is significant to develop rapid and non-destructive activation methods. This review summaries possible activation mechanisms, compares and analyzes various activation methods, and afterwards, proposes the design principles for activation. Some criteria for evaluating activation completion are also provided as references. Finally, the influence of several activation methods on cell durability is overviewed from present available researches. In this review, hydrogen pumping, short circuit, and cathode starvation are considered as more effective methods versus traditional approaches. The performance improvement after activation is ascribed to the change in membrane morphology, the reduction of contamination, and the optimization of catalyst layers. More importantly, five factors including high temperature, sufficient water, change in current or voltage, reductive atmosphere, and valid combination of different methods are highlighted in designing rapid activation procedures. Highlights: Several common activation mechanisms are summarized. Various activation procedures are further compared and analyzed. Internal relationship among multiple activation methods is discussed. Five principles of activation procedure design are proposed. Influence of several activation methods on cell durability is reviewed.